Recent Perspectives on Genome, Transmission, Clinical Manifestation, Diagnosis, Therapeutic Strategies, Vaccine Developments, and Challenges of Zika Virus Research - Shankar, Apoorva; Patil, Amulya A.; Skariyachan, Sinosh (Frontiers in Microbiology, 2017)
One of the potential threats to the public health microbiology in 21st century is the increased mortality rate caused by Zika virus (ZIKV), a mosquito-borne flavivirus. The raise in severity of ZIKV infection urged World Health Organization (WHO) to announce this virus as global concern. The limited knowledge on the structure of the virus, virulent factors and replication mechanism posed as hindrance for vaccine development against ZIKV. Several vector and non-vector borne forms of transmission are observed which aid in spreading the disease. The similarity of this virus with other flavivirus such as Dengue and West Nile Virus is worrisome and there are high scopes to undertake Zika virus research that probably provide insight for novel therapeutic intervention. Thus, this review focuses on the recent aspects of Zika virus research including the outbreak, genome structure, multiplication and propagation of the virus, current animal models, clinical manifestations, available treatment options (probable vaccines and therapeutics) including the advancements in computational drug discovery pipelines and challenges and limitation to undertake Zika viral research. The review suggests that the disease became one of the universal concerns and an interdisciplinary environment of in vitro cellular assays, Genomics, Proteomics and computational biology tools probably contribute insights for the screening of novel molecular targets for drug design. The review tried to provide cutting edge knowledge in Zika viral research with future insights required for the development of novel drugs